ChemInform Abstract: Zn‐Mediated Reduction of Oxalyl Chloride Forming CO and Its Application in Carbonylation Reactions. Issue 14 (March 2016) - Markovic, Martin; Lopatka, Pavol; Koos, Peter; Gracza, Tibor
Abstract: Oxalyl chloride is used as extremely efficient substitute for toxic gaseous CO in palladium‐catalyzed alkoxy‐/amino‐/hydrogen‐/hydroxycarbonylation reactions.